2022
DOI: 10.21926/obm.icm.2203028
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Prenatal Factors and Self-Reported Emotional Availability at 3- and 6-Months Postpartum

Abstract: Positive perceptions of pregnancy are associated with better postpartum outcomes, including stronger relationship with baby. Although better self-reported emotional availability (EA-SR) is associated with greater attachment security with infants, research has not yet explored the relationship between prenatal maternal factors and EA-SR. The aim of the study was to explore the associations between prenatal variables (adult attachment, shame, compassion) and EA-SR at 3- and 6-months postpartum. A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…EA Self-Report EA-SR: Assessment of Self-Reported or Perceived EA. Conducting an online, cross-sectional study, Caldwell et al (2022) found that self-compassion, psychological flexibility, experiences in close relationships, and shame (all self-reported) during the third trimester of pregnancy predicted significant percentage of the variance in the EA-SR at 6 months. Postnatally assessed psychological flexibility, self-compassion, and better breastfeeding experience (with infants less than 2 years of age, 11 months on average) correlated with the EA-SR (affect quality), according to Whittingham and Mitchell (2021).…”
Section: Resultsmentioning
confidence: 99%
“…EA Self-Report EA-SR: Assessment of Self-Reported or Perceived EA. Conducting an online, cross-sectional study, Caldwell et al (2022) found that self-compassion, psychological flexibility, experiences in close relationships, and shame (all self-reported) during the third trimester of pregnancy predicted significant percentage of the variance in the EA-SR at 6 months. Postnatally assessed psychological flexibility, self-compassion, and better breastfeeding experience (with infants less than 2 years of age, 11 months on average) correlated with the EA-SR (affect quality), according to Whittingham and Mitchell (2021).…”
Section: Resultsmentioning
confidence: 99%